(untitled) (Research, Society and Development, 2024)
The objective of this study was to analyze the variables: weight, body condition score (BCS) and rump height of 39 Nelore heifers, in the rearing phase, during the rainy season of the Cerrado. The animals were fed Brachiaria brizantha and B. decumbens pasture with free access to mineral salt. Through Pearson’s correlation for the variables, weight and BCS, as a function of age, it was found that the highest magnitudes were obtained in the variables weight: height ratio and between the variables weight and body condition score, concluding that these variables are strongly correlated. The magnitude of the correlation was moderate between the variables: rump height and weight and intermediate between the weight: height ratio and rump height and BCS and rump height. The parameters of weight, growth and body condition score had a quadratic and ascending behavior during the study period. The values of weight and BCS were lower than the data in the cited literature.